Research on Active Service Model with Personalized Education Resources - Yang, Qiang (Asian Journal of Contemporary Education, 2019)
In this paper, the learning process is digitally tracked and recorded, with regard to learning evolves into data-intensive learning. Also, the number and scale of data are long and the resources are heterogeneous, and the information resources are not abundant, causing users to be lost. In the process of clean information, seeking information about in our field is like a smart needle in the sea, triggering the screening and acquisition of personalized information resources. Consequently, the rapid development and widespread popularity of Internet technology has led to social inequality and differentiation, resulting in information polarization between the rich and the poor and the knowledge gap. Consequently, the rationality and balance of resource allocation directly affects the degree of achievement of educational equity, in terms of the active promotion of educational resources. In the results, the digital divide is essentially the unfairness of information rights, which will lead to cultural divides, political divides and social divides.